The Causal Factors Affecting the Business Performance of Thai Fruit Wholesale - Tasaen, Winussara; Taiwan, Anong (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
This research aimed at studying the causal factors affecting business performance of Thai fruit wholesale. A sample group were selected from wholesalers at Talaad Thai, Khlong Nueng Subdistrict, Khlong Luang District, Pathum Thani Province. The completed 600 questionnaires were collected. Data were analyzed using frequency, percentage, mean, standard deviation, Pearson’s correlations and SEM (Structural Equation Model). The results showed that the entrepreneurial orientation, value creation, service innovation and business performance were rated at highest level. Testing correlation among factors, all of them were correlated together significantly. The influence testing from structural equation model (SEM) revealed that service innovation factor was directly affected by entrepreneurial orientation at weight 0.877 (77 percent on predicting variable). And business performance was directly affected by entrepreneurial orientation, value creation and service innovation at weight 0.92, -0.49 and 0.49 respectively and it was indirectly affected by entrepreneurial orientation factor at weight -0.064. The highest total influence was on entrepreneurial focus with a value of 0.880. Focusing on entrepreneurship, service innovation, it had a significant effect on business operations at .01 and had a predictive coefficient of 78 and 85 percent, respectively.